Clinical Profile of Ocular Diseases at a Tertiary Eye Care Centre in Mid-Western Nepal - Basnet, Pragya Singh; Malla, Sagun; Sharma, Deepa; Gautam, Roshan (Nepalese Medical Journal, 2021)
Introduction: Nepal is a developing country where most of the population does not have access to proper health care services and on top of that eye care services do not reach the entire population. This study aimed to determine the pattern of ocular morbidity in patients attending the ophthalmic OPD of Rapti Academy of Health Sciences. Materials and Methods: This was a prospective cross-sectional study conducted in the Department of Ophthalmology of Rapti Academy of Health Science, Dang. The study period was Poush 2077 to Chaitra 2077. All the patients visiting the OPD of the Ophthalmology department with an ocular problem were included in the study. Results: A total of 1000 patients were examined during the study period. The patient's ages below 1 year were excluded so a total of 970 samples was selected. In which 625 (64.4%) were female and 345 (35.6%) were male. Most patients 92.9% were from Dang followed by Rolpa 4.1%, Rukum 1.4%, Pyuthan 0.9%, and Salyan 0.6%. Patients were examined from all age groups except for 1 year which was excluded. Out of the total patients, a maximum number of patients were female and the maximum number of patients were in the age group of 21- 30 years and followed by more than or equal to 60 years age group. Conclusions: This study will help in obtaining epidemiology of Ocular disease for proper planning and management in the hospital.